Synthesis on Push Pull Dichotomy and its Resulting Impact on Tourism Trends (Global Journal of Management and Business Research, 2013)
The dichotomy rallying behind the concepts of push and pull dimensions in the tourism paradigm with their underlying formulations are systematically analyzed. The factors relating to various forces that are motivating the tourist for travelling to different destinations are investigated along with role and influence of the cognitive mind by probing into traditional scriptures followed by systematic field surveys. The results of these studies indicated that motive motivation construct is corresponding to the Maslow’s hierarchy of needs tending towards actualization of travel experiences. The travel path from origin based push factors along with those forces which are pulling a tourist to the destination is conceptualized by design and development of a double engine locomotive resulting in dual stimulus curve. This stimulus is studied by analyzing the foreign and domestic tourist data that are found to be corresponding to the personal place bond and nationality for a given cultural context which explained tourism trends. Contrary to the popular belief in tourism literature, the present findings go on to show that both the organs-of-perception and organs-of-activity are to be in unison without any dissonance for realizing the maximum travel experiences.
Keywords: stimulation; cognition; emotion; mind; push pull engine